1999
DOI: 10.1021/jp9825213
|View full text |Cite
|
Sign up to set email alerts
|

Bromination Reactions Important in the Mechanism of the Belousov−Zhabotinsky System

Abstract: We investigate the kinetics of bromination of malonic acid, bromomalonic acid, tartronic acid, and ethanetetracarboxylic acid in 1 M sulfuric acid with bromine and hypobromous acid as brominating agents. In all cases the reaction occurs via the enol form of the acid, and the reaction products are brominated species. The possibility of bromide production in the reaction of malonic acid or bromomalonic acid with hypobromous acid can be ruled out. These results are important for the negative feedback loop in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 18 publications
3
66
0
Order By: Relevance
“…The more accepted hypothesis to explain the induction period is that a crucial concentration of the organic brominated species is necessary for the onset of the oscillatory regime. 5,6 The Györgyi-Turányi-Field (GTF) model 7 is one of the most complete mechanism for the BZ reaction, which is consistent with the hypothesis of a crucial concentration of the organic brominated species for the end of the induction period. According to the GTF model the induction period gets shorter as the bromate concentration increases, mainly because an increase in the bromate concentration involves an increase in the bromomalonic acid (BrMA) production via the reactions, (we use in this paper the notation of the original GTF model But contrary to the above well know hypothesis and mechanism, in a set of experiments we found that the induction period increases with the increasing initial bromate concentration.…”
Section: Introductionsupporting
confidence: 73%
“…The more accepted hypothesis to explain the induction period is that a crucial concentration of the organic brominated species is necessary for the onset of the oscillatory regime. 5,6 The Györgyi-Turányi-Field (GTF) model 7 is one of the most complete mechanism for the BZ reaction, which is consistent with the hypothesis of a crucial concentration of the organic brominated species for the end of the induction period. According to the GTF model the induction period gets shorter as the bromate concentration increases, mainly because an increase in the bromate concentration involves an increase in the bromomalonic acid (BrMA) production via the reactions, (we use in this paper the notation of the original GTF model But contrary to the above well know hypothesis and mechanism, in a set of experiments we found that the induction period increases with the increasing initial bromate concentration.…”
Section: Introductionsupporting
confidence: 73%
“…Under these conditions, the reaction scheme of Sirimungkala et al 18 2 (absorption at λ ) 400 nm) and Br -(bromide-selective electrode) are in good agreement with the corresponding simulated curves obtained using the reaction scheme in Appendix 1. To an accuracy of better than 10 -5 M, our measurements show that after complete bromination in accord with reaction R10 no MA or BrO 3 -are left in the reactor.…”
Section: Methodssupporting
confidence: 78%
“…According to Försterling,17,18 the concentration of Br 2 MA can be quite high if the sum of the initial bromide and bromate concentrations is comparable with [MA]. This situation occurs in many pattern formation experiments.…”
Section: Introductionmentioning
confidence: 97%
“…The most accepted hypothesis to explain the induction period of the BZ reaction is that a crucial concentration of the organic brominated species, mainly bromomalonic acid, must be reached before oscillation begins. 32 Thus, the results in Figure 6 can be understood by the effect Temperature / °C Figure 6 Effect of temperature on the duration of the induction period for the bulk solution of the BZ reaction as a control (black triangle), as well as for core (red diamond) and the core/pNIPMAm shell (blue square) microgels. The microgels (80 mM Ru(bpy) 3 ) were dispersed in aqueous solutions containing malonic acid (62.5 mM), NaBrO 3 (84 mM) and HNO 3 (0.3 M).…”
Section: Effect Of Nanoshell Addition On Oscillatory Behaviormentioning
confidence: 99%